Guide to igneous complexes in the region of geological survey training area of Siberian educational establishments (Eastern Kuznetsk Alatau slope) - Vasilyev B. D. Boris Dmitrievich (Tomsk, TPU Publishing House, 2006)
The given guide provides a description of igneous complexes in educational geological survey training region for students of Tomsk Polytechnic University, Tomsk and Novosibirsk State Universities, Krasnoyarsk University of Non-ferrous Metals and Gold. The Riphean, Paleozoic and Mesozoic igneous complexes of Kuznetsk Alatau, Batenevsk Mountain Range and southwestern Tchebakovo-Balakhtinsk basin in Minusinsk intermountain trough. The guide is designed for lecturers, researchers, postgraduates, and students in different geological specialties who are interested in Northern Khakassia magmatites.